Oxygen concentration and mobility in conserved archaeological wood. (17th November 2017) - Mortensen, Martin N.; Matthiesen, Henning
Abstract : Probes for measuring oxygen concentration were installed inside large samples of conserved wood from archaeological shipwrecks to record oxygen profiles as a function of depth under the wood surface. The concentration of oxygen was lower inside the wood than outside indicating that the supply of oxygen is limited and that oxygen is consumed within the material. This was confirmed by oxygen consumption rates averaging 1.3 ± 0.42 µg O2 /g wood/day. The diffusion properties were estimated by placing the wood samples in a nitrogen atmosphere and measuring nitrogen breakthrough time to the oxygen probes at different depths. A high level of variation was observed between the breakthrough times measured at different depths of the samples. This indicated that the access of oxygen is irregular, possibly due to wood heterogeneity and uneven distribution of conservation agent. By recording oxygen concentrations inside archaeological wood under stable environmental conditions, it was shown that oxygen concentration profiles are almost constant over a time span of seven years. This indicates that oxygen consumption, and thus oxidative degradation, is constant for an extended period of time. It also shows that the oxygen concentration inside conserved archaeological wood is a steady state value controlled by the local balance between oxygen supply and oxygen consumption.